Sulfuric acid and ammonia generation by bipolar membranes electrodialysis : transport rate model for lon and water through anion exchange membrane - Zhang, X. (Array, 2008)
Regeneration of sulfuric acid and ammonia from ammonium sulfate by bipolar membrane electrodialysis (BMED) coupling with stripping ammonia by air-blowing was studied. The result showed that it was feasible to regenerate sulfuric acid and ammonia from ammonium sulfate solution using this method. Empirical models to describe the ion and water transport behaviors through anion exchange membrane for BMED system were successfully developed. The models were valid to evaluate water transport rate and ion transport behavior for anion exchange membrane under similar operation conditions. Comparison of calculated values with experimental data indicated that the models were reliable to describe the water and ion transport behavior through anion exchange membrane for BMED system and could also be used to predict the water transport and ion transport behaviors for other current density under similar operation conditions